Definitions of Agile Software Development and Agility - Laanti, Maarit; Similä, Jouni; Abrahamsson, Pekka (Springer, 2013)
The Agile Manifesto and Agile Principles are typically referred to as the definitions of "agile" and "agility". However, many other definiti ons exist in the literature. Thus the different definitions provide in teresting source for research. For each definition we examine where th eir emphasis is and compare that to the emphases found in the Agile Pr inciples.